Hyaluronic acid-micelle casein concentrate hybrid particle and application thereof in emulsion gel
Through the use of hybrid particles prepared by micelle casein concentrate and sodium hyaluronate, problems of high internal phase emulsion gels in mechanical weaknesses, rheological challenges and environmental sensitivity are solved, achieving efficient and stable emulsion gel preparation for 3D printing and food science.
Patent Information
- Application Number
- CN202411990789.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art faces mechanical weaknesses, rheological challenges and environmental sensitivity when preparing high internal phase emulsion gels, and the batch stability of the traditional emulsion formulation casein is difficult to control, limiting the wide application of emulsion gels.
Hyaluronic acid-Micellar casein concentrate hybrid particles (HA-MCC hybrid particles) were prepared by micelle casein concentrate (MCC) and sodium hyaluronate (HA), and high internal phase emulsion gels with excellent structural properties, rheology, mechanical properties and 3D printing properties were prepared by the hybrid particles.
It achieves long-term stability of high internal phase emulsion gel, has excellent emulsification and foaming properties, and does not require additional crosslinking agents. It is suitable for clean label foods, and the preparation method is simple, fast and environmentally friendly.
Smart Images

Figure CN119798720A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to hyaluronic acid-micelle casein concentrate hybrid particles and application thereof in emulsion gel, belonging to the field of new materials. Background Art
[0002] O / W emulsions and O / W high internal phase emulsion gels have broad development prospects in the food and pharmaceutical, daily chemical products, and petrochemical industries. However, due to their thermodynamic instability, emulsion systems are prone to creaming, flocculation, aggregation, and Ostwald ripening, leading to instability, which is not conducive to their application in various fields. In order to stabilize the emulsion system, it is necessary to reasonably select particulate emulsifiers with excellent performance. The physicochemical and structural properties of particulate emulsifiers control their adsorption and assembly at the fluid interface, which is crucial for stabilizing systems such as emulsions and foams. Soft particles with excellent interfacial properties have high surface activity and emulsification properties, can be quickly adsorbed on the fluid interface and deform and collapse to form a viscoelastic interface layer to provide a mechanical barrier, thereby achieving the stability of foams and emulsions.
[0003] Milk is a natural biological fluid obtained during biological evolution, which can fix more calcium and inorganic phosphorus (Pi) without causing pathological calcification of the mammary gland. In order to prevent calcium phosphate precipitation, calcium-sensitive caseins (αs1-, αs2-, and β-caseins) fix amorphous calcium phosphate (ACP) nanoclusters to form a complex hierarchical assembly called casein micelles. Highly hydrated micelles are porous structures with many water-filled cavities and channels, with a polydisperse size distribution of 40% and an average diameter of 100 to 200 nm. α-Casein exists throughout the structure of casein micelles, β-casein exists mainly inside the micelles, and hairy κ-casein exists mainly in the surface area of the micelles to stabilize the micelles. Casein (also commonly known as casein, casein, lactic acid, casein, casein, casein, casein, casein, etc.), one of the traditional dairy ingredients, is a product obtained by skimming fresh milk, adding acid (lactic acid, acetic acid, hydrochloric acid or sulfuric acid), adjusting the pH to 4.8, so that the casein micelles lose their charge and coagulate and precipitate. When used, alkali needs to be added to adjust the pH to an alkaline environment before it can be further used. In this process, most of the casein will lose its micellar structure and become a mixture of different casein components (αs1-, αs2-, β- and κ-casein). Compared with whey protein, which has better emulsification, the application and development of casein in traditional dairy ingredients are relatively limited. With the advancement of membrane separation technology, the industrialization of micellar casein has gradually become large-scale. Micellar casein retains the original micellar structure in milk and does not need to adjust the pH to an alkaline environment to dissolve. It has emulsification and foaming properties comparable to whey protein, and has a wider range of application scenarios in the fields of food, medicine, health products, and chemical engineering. More importantly, compared with whey protein, a by-product of cheese processing, milk protein concentrates (MPC) and casein micelles are gradually becoming better choices.
[0004] High-internal phase emulsions (HIPEs) have broad development potential and application space in daily chemical products, food and medicine, and even petrochemical industries. HIPEs can be used to prepare porous materials with different properties, and can be applied to some high-tech fields closely related to people's lives, such as filter membranes, organic semiconductors, and tissue engineering scaffolds. They can also serve as food and drug carriers to transport and release active substances in the human body. With the increasing demand for "clean labels", the application of some inorganic materials and chemical synthetic materials in the food field has been greatly limited. For natural materials as particulate emulsifiers, they are not only low in cost, small in dosage, high in safety, and less in environmental pollution, but also can give HIPEs good emulsification stability, a wide range of applications and high development potential. At present, a key challenge is to find a more low-energy, environmentally friendly, simple, easy, time-saving and labor-saving method for preparing food-grade particulate emulsifiers, and the produced particulate emulsifiers should have excellent performance, high safety, and be able to achieve industrial-scale production and commercial application. Casein micelles are complex hierarchical assemblies with porous structures. After being adsorbed to the interface, there are more deformation possibilities. They are good particle emulsifiers. The Chinese patent application document with publication number CN118476605A has disclosed that MPC rich in casein micelles is a gel particle with uneven cross-linking (the cross-linking density inside the particles shows regional differences), which has the advantages of both hard particles and soft particles (that is, the area with higher cross-linking density is similar to hard particles, while the area with lower cross-linking density is similar to soft particles), and exhibits spontaneous adsorption and limited compliance (the stiffness / softness of the particles can be adjusted). Since there is no obvious energy barrier for interfacial adsorption, it is conducive to improving foaming ability and emulsifying activity; in addition, limited compliance can resist Ostwald ripening, thereby achieving long-lasting emulsion stability.
[0005] With the further integration of three-dimensional (3D) printing technology and food science, the creation of personalized and structurally complex foods has posed more challenges to the performance of food materials. Among various printable materials, high-internal phase emulsion gels (HIPE gels) stand out due to their high oil content and tunable rheological properties, making them promising candidates for food-grade 3D printing. However, the widespread adoption of HIPE emulsion gels in practical applications is hindered by mechanical weaknesses, rheological challenges, and environmental sensitivity. Protein-stabilized food-grade HIPE gels are highly valued for their natural emulsifying properties and compatibility with clean label formulations. However, their use in 3D printing is limited by insufficient mechanical strength, which compromises the stability of printed structures and leads to problems such as layer collapse. Balancing the shear-thinning behavior during extrusion and rapid recovery after deposition remains difficult, further compromising structural integrity. In addition, environmental factors such as pH, temperature, and ionic strength can unpredictably affect gelation and stability.
[0006] Traditional strategies to improve the performance of HIPE emulsion gels, such as chemical modification, thermal processing, and ionic crosslinking, often impair the natural functionality or bioactivity of the material. In addition, weak interfacial adhesion between layers remains a major challenge, hindering the fabrication of strong and visually attractive structures. HIPE emulsion gels have a wide range of application systems, superior performance, and high internal phase (oil phase) content, which is particularly important for printing foods with complex structures and fine shapes. The stability and plasticity of high internal phase emulsion gels make them ideal materials for 3D food printing, which can meet the high requirements of food printing for material properties.
[0007] Prior art (Emulsions stabilized by casein and hyaluronic acid: Effects of high intensity ultrasound on the stability and vitamin E digestive characteristics. Ultrasonics Sonochemistry, 94.) discloses an emulsion stabilized by an ultrasonically treated casein (CAS)-hyaluronic acid (HA) complex, which is prepared by preparing a CAS solution (3%, w / v), then adjusting the pH value of the solution to 7.0 with 1.0 mol / L NaOH, and then mixing the CAS solution with HA (194 kDa) powder to obtain a CAS-HA complex with a HA concentration of 0.5% (w / v) as an aqueous phase, soybean oil as an oil phase, and dissolving vitamin E in the soybean oil. The emulsion is prepared with an oil / water volume ratio of 20 / 80. This prior art has the problem of consistency with the traditional dairy ingredient casein, that is, the casein raw material needs to be dissolved under alkaline conditions. As mentioned above, the mixture composition of each batch of such raw materials in the industry is uncontrollable. In addition, this study only reports 20% of the oil phase composition. The preparation of emulsions with a higher oil phase may require further cross-linking of the protein in the water phase or the addition of more food stabilizers.
[0008] Existing technology (Fabrication of flavor oil high internal phase emulsions by casein / pectin hybrid particles: 3D printing performance.FoodChemistry.2022Mar;371:131349.DOI:10.1016 / j.foodchem.2021.131349) discloses a 3D printable oil / water (O / W) high internal phase emulsion (internal phase fraction of 75%) prepared by casein / pectin hybrid particles and flavor oil, the pH value of the 3% (w / v) casein solution is adjusted to 11, pectin is added to an aqueous phase containing 3% (w / v) casein and pectin, with concentrations of 1% (w / v), 2% (w / v), 3% (w / v), 4% (w / v) and 5% (w / v), respectively, and the pH value of the solution is adjusted to 3; flavor oil is added to the casein-pectin mixture to obtain a mixture with a water phase: oil phase mass ratio of 1:3, and a high internal phase emulsion is obtained after homogenization. This prior art still uses the traditional milk ingredient casein, and the raw material needs to be dissolved in an environment of pH 11. As mentioned above, the composition of each batch of such raw materials in the industry is uncontrollable. In addition, this prior art only reports the acquisition of a proteoglycan complex in a solution of pH 3. In fact, the pectin raw material itself is extremely complex. It is an anionic polysaccharide with a complex structure extracted from the cell wall of higher plants. Different plant sources and preparation processes will significantly affect the molecular structure and functional properties of pectin, including: monosaccharide composition, domain ratio, degree of esterification and degree of branching. Generally speaking, pectin is more stable in acidic solutions than in alkaline solutions, and this pectin is difficult to dissolve in pure water and needs to be heated to about 60°C before it can be dissolved. In addition, when the pectin is dissolved in pure water at a concentration of 1%, the pH of the solution is about 3.3, which is relatively unfavorable for the relevant research of proteoglycans. In view of the existence of the isoelectric point of the protein, the polysaccharide solution of about pH 3 is equivalent to a precipitant for the protein with an isoelectric point of about 2 to 4; although the pH of the solution can be adjusted to near neutrality by adding alkali, acid-base neutralization will also generate more salts, and for the research of proteins, the introduction of salts will lead to more discussion factors, such as whether it leads to the salt dissolution effect or the salting-out effect of the protein. In the research of proteins, the type of ions (cations, anions), valence (monovalent ions, divalent ions, trivalent ions, etc.) and their strength will have a complex effect on the structure and properties of the protein. The casein-pectin reported in this prior art can stabilize 75% of the oil phase, which may only be stably obtained in a solution of pH 3, and the too narrow pH stability range will make this system very limited even if it is applied in the food industry.
[0009] Prior art (Development and characterization of a casein-hyaluronic acidemulsion gel with high water-holding capacity and excellent rheologicalproperties for 3D printing.Food Hydrocolloids. https: / / doi.org / 10.1016 / j.foodhyd.2023.108632) discloses that the addition of hyaluronic acid (HA) can enhance the rheological properties and printability of casein (CAS) emulsion gel, wherein CAS powder is dispersed in water, NaOH is added to adjust the pH to 7.0, and a casein solution (8%, w / v) is prepared; the CAS solution is then supplemented to 500 mL with water, and different amounts of HA powder are added to the CAS solution (30 mL), and CAS-HA solutions with HA concentrations of 0.02, 0.04, 0.06, 0.08, 0.1 and 0.2% w / v are used as the aqueous phase, and the oil phase / aqueous phase volume ratio is controlled at 20 / 80 to obtain an emulsion, and finally GDL (4%, w / v) is added to obtain an emulsion gel. This prior art still uses the traditional milk ingredient casein, and NaOH needs to be added to dissolve the raw materials. As mentioned above, the composition of the mixture of each batch of such raw materials in the industry is uncontrollable. In addition, in order to obtain stable interfacial emulsified particles, the prior art requires the use of GDL for cross-linking to further stabilize the emulsion with an oil phase of 20%. The addition of the cross-linking agent will solidify the structure of the interfacial emulsified particles, limiting the adjustability of the interfacial properties of the emulsion.
[0010] In summary, the current existing technologies are basically centered around the traditional dairy ingredient casein. As a raw material with difficult batch stability control, it faces many technical problems in use. Most studies can only stabilize a lower oil phase ratio, or stabilize a higher oil phase ratio at a specific pH value after combining with polysaccharides, or require the addition of additional cross-linking agents to obtain better stability properties. Therefore, in order to more easily prepare emulsion gels with a wider range of application scenarios, it is necessary to design a clean label food soft particle that can stabilize high internal phase emulsion gels for a long time. Summary of the invention
[0011] In order to solve the above problems, the present invention uses micellar casein concentrate (MCC) and sodium hyaluronate (HA) of a certain molecular weight, based on a very simple, rapid and environmentally friendly green industrial technology, to prepare HA-MCC hybrid particles with excellent performance; the HA-MCC hybrid particles are used to prepare a high internal phase emulsion gel with excellent structural properties, rheological properties, mechanical properties and 3D printing properties. The present invention provides great potential for the combination of 3D printing and food science.
[0012] The present invention provides a method for preparing hyaluronic acid-micelle casein concentrate hybrid particles (HA-MCC hybrid particles) by using micellar casein concentrate (MCC) and sodium hyaluronate (HA), the method comprising:
[0013] Micellar casein concentrate (MCC) is dispersed in water, mixed and homogenized; sodium hyaluronate (HA) is added and stirred to obtain HA-MCC hybrid particles.
[0014] In one embodiment of the present invention, the final concentration of the micellar casein concentrate (MCC) in water is 1% to 5% (w / w);
[0015] Preferably, the final concentration is 5% (w / w).
[0016] In one embodiment of the present invention, the mixing condition is 40-60° C. for 0.5-3 hours;
[0017] Preferably, the mixing is carried out at 50° C. for 2 hours.
[0018] In one embodiment of the present invention, the homogenization condition is homogenization at a pressure of 0 to 150 MPa (but not 0), and homogenization is performed 3 to 6 times;
[0019] Preferably, the homogenization is performed at 90 MPa for 3 times.
[0020] In one embodiment of the present invention, the molecular weight of the sodium hyaluronate is 100 to 1090 kDa;
[0021] Preferably, the molecular weight of the sodium hyaluronate is 200 to 600 kDa;
[0022] More preferably, the molecular weight of the sodium hyaluronate is 400 kDa.
[0023] In one embodiment of the present invention, the amount of sodium hyaluronate added is 0 to 1.0% (w / v) (but not 0);
[0024] Preferably, the added amount of sodium hyaluronate is 1.0% (w / v).
[0025] In one embodiment of the present invention, the stirring condition is 200-800 rpm for 8-12 hours.
[0026] The present invention also provides HA-MCC hybrid particles prepared by the above preparation method.
[0027] The present invention also provides the use of the above-mentioned HA-MCC hybrid particles in the fields of food, health products, cosmetics, daily chemicals or biomedicine, wherein the application is to encapsulate and deliver bioactive substances, gel liquid oils, or prepare emulsions, foams, emulsion gels or high internal phase emulsion gels, etc., and further includes using these materials in the preparation of food, health products, biomedicine, daily chemicals, etc., which helps to create advanced materials with structural hierarchy and complex interface functions.
[0028] In one embodiment of the present invention, the food includes but is not limited to mayonnaise, salad dressing and the like.
[0029] The present invention also provides a method for preparing an emulsion gel using the above HA-MCC hybrid particles, the method comprising:
[0030] The HA-MCC hybrid particles are used as the water phase, the water phase is mixed with the oil phase, and dispersed by high-speed shearing to obtain an emulsion gel.
[0031] In one embodiment of the present invention, the volume ratio of the oil phase to the water phase is (0:100) to (85:15), but not zero.
[0032] In one embodiment of the present invention, the rotation speed of the high-speed shearing is 10000-12000 rpm.
[0033] The present invention also provides a method for preparing a high internal phase emulsion gel using the above HA-MCC hybrid particles, the method comprising:
[0034] The HA-MCC hybrid particles are used as the aqueous phase, the aqueous phase is mixed with the oil phase, and dispersed by high-speed shearing to obtain a high internal phase emulsion gel; the volume ratio of the aqueous phase to the oil phase is (0:100) to (15:85), but not 0.
[0035] In one embodiment of the present invention, the volume ratio of the water phase to the oil phase is 1:3.
[0036] In one embodiment of the present invention, the water phase and the oil phase are mixed by dropping the water phase into the oil phase at a dropping speed of 50-70 drops / minute.
[0037] In one embodiment of the present invention, the rotation speed of the high-speed shearing is 10000-12000 rpm.
[0038] In one embodiment of the present invention, the oil phase includes but is not limited to soybean oil, corn oil, rapeseed oil, sunflower oil, palm oil, castor oil, conjugated linoleic acid, and linolenic acid.
[0039] In one embodiment of the present invention, the oil phase may also be added with lipophilic food nutrients such as curcumin, β-carotene, astaxanthin, lycopene, vitamin E, n-3 fatty acids, vitamin A, etc.
[0040] The present invention also provides an emulsion gel or a high internal phase emulsion gel obtained by the above preparation method.
[0041] The present invention also provides application of the high internal phase emulsion gel in a fat-soluble active ingredient carrier.
[0042] In one embodiment of the present invention, the fat-soluble active ingredients include but are not limited to curcumin, β-carotene, astaxanthin, lycopene, vitamin E, n-3 fatty acids, vitamin A, resveratrol, and capsaicin.
[0043] The present invention also provides the use of the above-mentioned HA-MCC hybrid particles or the above-mentioned high internal phase emulsion gel in 3D printed food.
[0044] In one embodiment of the present invention, the application is to use a 3D printer to perform emulsion gel 3D printing using the above-mentioned high internal phase emulsion gel.
[0045] In one embodiment of the present invention, when a 3D printer is used for emulsion gel 3D printing in the application, the 3D printing model is a cuboid (24.00 mm×24.00 mm×15.00 mm); the nozzle diameter is 0.8 mm, the printing speed is 28 mm / s, and it is carried out at room temperature.
[0046] The present invention also provides a 3D printed food based on the above-mentioned high internal phase emulsion gel, wherein the food is obtained by 3D printing using the HA-MCC hybrid particles prepared by the above-mentioned method or the above-mentioned high internal phase emulsion gel.
[0047] In one embodiment of the present invention, the food is an easy-to-swallow food.
[0048] Beneficial effects:
[0049] (1) The HA-MCC hybrid particles prepared by the present invention have good interface properties.
[0050] (2) The present invention utilizes HA-MCC hybrid particles to prepare emulsion gels, and the internal phase (oil phase) fraction can be 0 to 85%; the present invention utilizes HA-MCC hybrid particles to prepare high internal phase emulsion gels, and the internal phase (oil phase) fraction can reach 80%, which has excellent emulsification and foaming properties.
[0051] (3) The emulsion gel prepared by the present invention can be used to prepare clean label food without adding additional cross-linking agents; it is economical, low-cost, simple in method, and can be industrialized; the preparation method of the present invention is very simple, fast and environmentally friendly.
[0052] (4) The hybrid particles and emulsion gel prepared by using micellar casein concentrate (MCC) of the present invention are widely used in the food field, not only in alkaline systems, but also in neutral systems or under acidic conditions.
[0053] (5) The present invention develops HA-MCC stabilized high internal phase emulsion gels with enhanced properties, capable of creating complex 3D printed shapes, which can create culturally and aesthetically significant foods. The present invention offers great potential for combining 3D printing with food science, making complex and customized food design possible.
[0054] (6) The high internal phase emulsion gel prepared by the present invention can be used as a carrier for encapsulating fat-soluble active ingredients such as curcumin, thereby improving bioavailability and having wide application value in food delivery systems.
[0055] (7) The high internal phase emulsion gel of the present invention shows potential application prospects in the care of dysphagia. Through the food 3D printing technology, it solves the problem of easy-to-swallow food being paste-like / muddy, improves the dietary pleasure of people with dysphagia, increases oral intake, and significantly improves the quality of life. The gel of the present invention provides individuals with dysphagia with a safe, nutritionally balanced, and visually attractive choice, enhancing safety and dining experience. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The FTIR test results are shown in Figure 1. MCC is micellar casein concentrate; L-HA is HA with a molecular weight of 100 kDa; H-LA is HA with a molecular weight of 400 kDa; L-HA 0.1 -MCC is the HA-MCC hybrid particles prepared in Example 4 using HA with a molecular weight of 100 kDa and an addition amount of 0.1%; L-HA 1.0 -MCC is the HA-MCC hybrid particles prepared in Example 2 using HA with a molecular weight of 100 kDa and an addition amount of 1.0%; H-HA 0.1 -MCC is the HA-MCC hybrid particles prepared in Example 3 using HA with a molecular weight of 400 kDa and an addition amount of 0.1%; H-HA 1.0 -MCC is the HA-MCC hybrid particles prepared in Example 1 using HA with a molecular weight of 400 kDa and an addition amount of 1.0%.
[0057] Figure 2 The scanning electron micrographs of MCC freeze-dried solution and HA-MCC hybrid particles; M is micellar casein concentrate; L-HA / M 0.1 HA-MCC hybrid particles prepared in Example 4 using HA with a molecular weight of 100 kDa and an addition amount of 0.1%; L-HA / M 1.0 HA-MCC hybrid particles prepared in Example 2 using HA with a molecular weight of 100 kDa and an addition amount of 1.0%; H-HA / M 0.1 HA-MCC hybrid particles prepared in Example 3 using HA with a molecular weight of 400 kDa and an addition amount of 0.1%; H-HA / M 1.0 The HA-MCC hybrid particles were prepared in Example 1 using HA with a molecular weight of 400 kDa and an addition amount of 1.0%.
[0058] Figure 3 This is the visual appearance of the emulsion gel obtained in Comparative Example 4.
[0059] Figure 4 The rheological properties of HIPE gels are shown in Figure 1. (a) Relationship between apparent viscosity and shear rate; (b) Three-stage incremental shear thinning test (3-ITT); (c) Creep recovery curve; (d) Scanning storage modulus (G′); (e) Scanning loss modulus (G″); (f) Average loss tangent (tanδ); MCC is a high internal phase emulsion gel stabilized only with micellar casein concentrate; L-HA 0.1 -MCC is the emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 4 as the aqueous phase; L-HA 1.0 -MCC is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles (HA molecular weight of 100 kDa) of Example 2 as the aqueous phase; H-HA 0.1 -MCC is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 3 as the aqueous phase; H-HA 1.0 - MCC is the emulsion gel prepared in Example 6.
[0060] Figure 5Graphs showing the stability analysis results of HIPE gels; wherein (AE) are transmittance curves of a high internal phase emulsion gel (A) stabilized only with micellar casein concentrate, an emulsion gel (B) prepared in Example 11 using the HA-MCC hybrid particles of Example 4 as the aqueous phase, an emulsion gel (C) prepared in Example 11 using the HA-MCC hybrid particles of Example 3 as the aqueous phase, an emulsion gel (D) prepared in Example 11 using the HA-MCC hybrid particles (HA with a molecular weight of 100 kDa) of Example 2 as the aqueous phase, and an emulsion gel sample (E) prepared in Example 6 during centrifugation, reflecting their stability; (F) is a visual comparison of the appearance of the HIPE gel captured by LUMiSizer before (upper row) and after (lower row) centrifugation.
[0061] Figure 6 The visual appearance (a) and CLSM observation (b) of HIPE gel; MCC is a high internal phase emulsion gel stabilized only by micellar casein concentrate; L-HA 0.1 -MCC is the emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 4 as the aqueous phase; L-HA 1.0 -MCC is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles (HA molecular weight of 100 kDa) of Example 2 as the aqueous phase; H-HA 0.1 -MCC is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 3 as the aqueous phase; H-HA 1.0 - MCC is the emulsion gel prepared in Example 6.
[0062] Figure 7 : is a result diagram of HIPE gel swallowing performance; wherein, MCC is a high internal phase emulsion gel stabilized only with micellar casein concentrate; 0.1% 100HA-M is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 4 as the aqueous phase; 1.0% 100HA-M is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 2 (HA molecular weight of 100 kDa) as the aqueous phase; 0.1% 400HA-M is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 3 as the aqueous phase; 1.0% 400HA-M is an emulsion gel prepared in Example 6.
[0063] Figure 8 This is a visual appearance picture of HIPE gels of different colors obtained in Example 12.
[0064] Fig. 9HIPE gel 3D printing visual images; (a) the fresh appearance of the gel 3D printed blocks prepared in Example 6 and Example 11 and the appearance after standing for 30 and 60 minutes; (b) the yellow high internal phase emulsion gel 3D printed flowers and bows prepared in Example 12; MCC is a high internal phase emulsion gel stabilized only with micellar casein concentrate; L-HA 0.1 -MCC is the emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 4 as the aqueous phase; L-HA 1.0 -MCC is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles (HA molecular weight of 100 kDa) of Example 2 as the aqueous phase; H-HA 0.1 -MCC is an emulsion gel prepared in Example 11 using the HA-MCC hybrid particles of Example 3 as the aqueous phase; H-HA 1.0 - MCC is the emulsion gel prepared in Example 6. DETAILED DESCRIPTION
[0065] The following is a detailed description of an embodiment of the present invention in conjunction with the accompanying drawings: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0066] The materials involved in the following embodiments are as follows:
[0067] Micellar casein concentrate (MCC) was purchased from Leprino Foods, Denver, USA, and its composition was: protein 91.81%, carbohydrate 0.00%, ash 6.46%, moisture 5.76%, and fat 1.64%;
[0068] Casein (CAS) was purchased from Shangri-La Kangmei Dairy Development Co., Ltd.;
[0069] Pectin was purchased from Sigma-Aldrich Co (St. Louis, America), CAS No.: 9000-69-5;
[0070] Milk protein concentrate (MPC) was purchased from Fonterra Limited, New Zealand, model number MPC485;
[0071] Soybean oil was purchased from Yihai Kerry Arawana Holdings Co., Ltd. (Shanghai, China);
[0072] Fast green was purchased from Sigma-Aldrich Co (St. Louis, America);
[0073] Nile red was purchased from Aladdin Reagent Co, Ltd (Jinan, China);
[0074] Curcumin was purchased from Shanghai Wokai Biotechnology Co., Ltd. (Shanghai, China).
[0075] The methods involved in the following embodiments are as follows:
[0076] 1. Fourier transform infrared spectroscopy (FTIR)
[0077] The hybrid particles were freeze-dried at -80 °C for 48 h and their FTIR spectra were recorded using an FTIR spectrometer (Frontier, Perkin Elmer). All spectra were scanned 32 times in the range of 4000-400 cm-1 with air as the background and the average value was obtained.
[0078] 2. Measurement of particle size and zeta potential
[0079] Dynamic light scattering (DLS) was used to measure the particle size of the hybrid particle solution at an angle of 90° using a 4 mW He / Ne laser beam (λ = 633 nm);
[0080] During the measurement, the solution was diluted 50 times with ultrapure water, the pH of the solution was adjusted to neutral, the refractive indices of the dispersion medium and protein were set to 1.33 and 1.57, respectively, and the zeta potential was measured at 25°C.
[0081] 3. Scanning electron microscopy observation
[0082] The samples were quickly frozen in liquid nitrogen and freeze-dried at −50 °C for 48 h. The dried samples were placed on a stub using double-sided tape and coated with a 15 nm layer of gold-palladium using a sputter coater. The morphology of the fractured cross-section was observed under a scanning electron microscope (TM3030, Hitachi) at an accelerating voltage of 15.0 kV.
[0083] 4. Gel strength determination
[0084] The gel strength was measured using a texture analyzer (TA).
[0085] In TPA mode, select P / 25R probe, set the speed before, during and after measurement to 1.0, 2.0 and 2.0 mm / s respectively, the compression strain to 50%, and the trigger force to 5.0 g.
[0086] 5. Determination of rheological properties
[0087] The rheological properties of the emulsion gel were evaluated using a 25 mm parallel plate rheometer (MCR 92, Anton Paar).
[0088] The gap between the plates was set to 1000 μm; viscosity measurements were performed at shear rates ranging from 0.1 to 100 s;
[0089] The power law model (Formula 1) was used to fit the curve of apparent viscosity versus shear rate (method reference Improvement of 3D Printing Performance of Whey Protein Isolate Emulsion Gels by Regulating Rheological Properties: Effect of Polysaccharides Incorporation. Food and Bioprocess Technology. https: / / doi.org / 10.1007 / s11947-024-03488-9):
[0090] τ=Kγ n (1)
[0091] Where τ is the shear force (Pa); K is the consistency coefficient (Pa·s); γ is the shear rate s -1 ; n is the mobility index (dimensionless), n represents the deviation from the Newtonian model.
[0092] The linear viscoelastic region (LVR) was determined by scanning the emulsion gel at an amplitude of 0.01 to 10% at a frequency of 1.0 Hz;
[0093] A frequency sweep was performed in the range of 0.1–10 Hz at a constant strain of 0.1% to capture the changes in the dynamic modulus in the linear viscoelastic region;
[0094] For creep tests, a constant stress of 10 Pa was applied for 3 min, followed by stress removal and a 3 min recovery phase during which shear strain was monitored; the 3-stage thixotropy test (3-ITT) included a 1 s -1 (60 seconds), 100s -1 (5 seconds) and 1s -1 The shear rate stage (over 120 seconds) shows the change in viscosity over time;
[0095] The large amplitude oscillatory shear (LAOS) test frequency was 1.0 Hz, the temperature was constant at 25°C, and the strain range was 0.1% to 1000%. The original waveform data at different strains (10%, 100%, 1000%) at 1.0 Hz were collected, and the Lissajous curve was obtained using the MITlaos program.
[0096] 6. Determination of water holding capacity (WHC) and oil holding capacity (OHC)
[0097] The WHC and OHC of the emulsion gels were measured according to the method described in the prior art (Rheological property, β-carotene stability and 3D printing characteristic of whey protein isolate emulsion gels by adding different polysaccharides Food Chemistry. 2023 Jul; 414: 135702. DOI: 10.1016 / j.foodchem.2023.135702.) with slight modifications:
[0098] The sample (20 g) was placed in a 50 mL centrifuge tube and centrifuged at 8000 rpm for 30 minutes at 4°C. After centrifugation, the water and oil released due to the centrifugal force were removed and weighed. The WHC and OHC of the emulsion gel were calculated by formula (2) and formula (3):
[0099]
[0100] Among them, W T is the weight of the sample before centrifugation, W F and W O are the weights of water and oil released after centrifugation, respectively.
[0101] 7. Determination of gel stability
[0102] The effects of temperature and centrifugal force on gel stability were investigated using LUMiSizer 651 dispersion analyzer.
[0103] During the test, near-infrared light (865 nm) was transmitted through the sample, and the intensity of the transmitted light was measured as a function of position and time; the conditions were set at 25 °C, 3000 rpm, and 150 min, and the transmission intensity was recorded every 10 s; the transmission profile was analyzed using STEP View software (LUM GmbH) to calculate the instability index.
[0104] 6. Gel microstructure
[0105] The microstructure of the emulsion gel was observed using a confocal laser scanning microscope (CLSM) (TCS SP8, Leica).
[0106] The oil phase (red) is stained with Nile red, and the protein phase (green) is stained with fast green. Nile red (concentration of 1% w / v, solvent is ethanol) is mixed with the oil phase at a ratio of 1:100 (v / v), and fast green (concentration of 1% w / v, solvent is water) is mixed with the protein solution (aqueous phase solution) at a ratio of 1:100 (v / v); the stained sample is placed in the dark for 30 minutes, and then the stained protein solution (aqueous phase solution) is mixed with the stained oil phase according to the method in Example 6 or Example 11 to prepare a gel; a small amount of the stained gel sample is placed on a glass slide, spread evenly, and sealed with a cover; the microscope objective is set to 20 times, and the image is further magnified by 2 times using LAS X software; the excitation wavelengths of Nile red and fast green are 552nm and 638nm, respectively.
[0107] 7. Determination of gel 3D printing performance
[0108] Emulsion gel 3D printing was performed using a 3D printer (FOODBOT-S2, Shiyin).
[0109] The 3D printing model is a cuboid (24.00 mm × 24.00 mm × 15.00 mm); the nozzle diameter is 0.8 mm, the printing speed is 28 mm / s, and it is carried out at room temperature; after printing, the plane size (Ls, mm) and height (H0, mm) of the 3D printed product are measured using a vernier caliper, and the 3D printing accuracy (%) is calculated according to formula (4); then the printed product is placed at room temperature (25 ° C) for 60 minutes, the height (H60, mm) is measured, and the 3D printing stability (%) is calculated using formula (5):
[0110]
[0111] Where, L s L is the plane size of the 3D printed object, in millimeters (mm); m is the expected size of the 3D printed model, in millimeters; H0 is the initial height of the 3D printed object at 0 minutes, H 60 It is the height after standing for 60 minutes, in millimeters.
[0112] 8. Determination of IDDSI
[0113] Following the International Dysphagia Diet Standardization Initiative (IDDSI framework), the samples were subjected to the spoon tilt test, fork drop test, and fork pressure test using the IDDSI test methods.
[0114] The spoon tilt test mainly tests the adhesion of food. IDDSI shows that foods with greater adhesion will not be suitable for recommendation to the target population.
[0115] With the fork drop test, foods can be classified as level 3, 4, or 5. For level 3 (liquid) foods, it may drip slowly through the slits of the fork. For level 4 (puréed) foods, it may accumulate on the fork or a small amount may flow out from the slits of the fork and form a tail, but it should not flow out or drip continuously. For level 5 foods (moist and finely chopped), it will accumulate on the fork and will not easily or at all pass through the slits of the fork and will not form a tail.
[0116] The fork pressure test can distinguish food of grade 5 and above. In the fork pressure test, food of grade 5 does not need a force that causes the space between the thumbs to turn white (<17kPa) to be pressed into a suitable size (<4mm). For food of grade 6 (soft and bite-sized) and grade 7 (conventional), when cutting them into a suitable size, the space between the thumbs will turn white (>17kPa) during the fork pressure test, and a greater force is required.
[0117] Example 1: Preparation of HA-MCC hybrid particles
[0118] (1) dispersing micellar casein concentrate (MCC) in deionized water to a final concentration of 5% (w / w) to obtain an MCC solution; mixing the MCC solution at 50° C. for 2 hours, and then homogenizing three times on a high-pressure homogenizer (AMH-3, ATS) at an average pressure of 90 MPa;
[0119] (2) Sodium hyaluronate (HA) with a molecular weight of 400 kDa was added to the homogenized MCC solution obtained in step (1) at an amount of 1.0% (w / v, g / mL), and stirred at 500 rpm for 12 h at 4° C. to obtain HA-MCC hybrid particles.
[0120] Example 2: Optimization of Molecular Weight of Sodium Hyaluronate
[0121] The specific implementation method is the same as Example 1, except that the sodium hyaluronate (HA) with a molecular weight of 400 kDa in step (2) is replaced by sodium hyaluronate (HA) with a molecular weight of 100 kDa, 600 kDa or 1090 kDa; the remaining steps are the same as Example 1 to obtain HA-MCC hybrid particles.
[0122] Example 3: Optimization of the amount of sodium hyaluronate added
[0123] The specific implementation method is the same as Example 1, except that the amount of sodium hyaluronate (HA) added in step (2) is replaced by 0.1% (w / v, g / mL) from 1.0% (w / v, g / mL); the remaining steps are the same as Example 1 to obtain HA-MCC hybrid particles.
[0124] Example 4: Optimization of the molecular weight and addition amount of sodium hyaluronate
[0125] The specific implementation method is the same as Example 1, except that the sodium hyaluronate (HA) with a molecular weight of 400 kDa in step (2) is replaced by sodium hyaluronate (HA) with a molecular weight of 100 kDa, and the addition amount of sodium hyaluronate (HA) in step (2) is replaced from 1.0% (w / v, g / mL) to 0.1% (w / v, g / mL); the remaining steps are the same as Example 1 to obtain HA-MCC hybrid particles.
[0126] Example 5: Optimization of the amount of micellar casein concentrate (MCC) added
[0127] The specific implementation method is the same as Example 1, except that the addition amount of micellar casein concentrate (MCC) in step (1) is replaced by 5% (w / w) to 1%, 2%, 3% and 4% (w / w); the remaining steps are the same as Example 1 to obtain HA-MCC hybrid particles.
[0128] In addition, MCC added at 6% (w / w) was difficult to dissolve, and the viscosity after dissolution was too high to be conducive to homogenization;
[0129] When the MCC concentration is less than 1% (w / w), even if the particle emulsifier is formed, it cannot form a complete coverage at the interface.
[0130] Comparative Example 1: Preparation of HA-CAS hybrid particles
[0131] The specific implementation method is the same as Example 1, except that the micellar casein concentrate (MCC) in step (1) is replaced by casein (CAS), and the remaining steps are the same as Example 1 to obtain HA-CAS hybrid particles.
[0132] Comparative Example 2: Preparation of Pectin-MCC Hybrid Granules
[0133] The specific implementation method is the same as that of Example 1, except that the sodium hyaluronate (HA) with a molecular weight of 400 kDa in step (2) is replaced by pectin; the remaining steps are the same as those of Example 1.
[0134] The results showed that the pH of 1% (w / w) pectin dissolved was 3.32. When pectin was mixed with MCC at a final concentration of 5% (w / w), floccules appeared immediately and the pH of the solution was 5.81.
[0135] If it is necessary to obtain a stably dispersed pectin-MCC hybrid particle complex that can be used for particle size potential testing, the pectin needs to be diluted 50 times and the MCC needs to be diluted 50 times accordingly; at this time, pectin-MCC hybrid particles are obtained, and the pH of the solution of the pectin-MCC hybrid particles is 6.96.
[0136] Comparative Example 3: Preparation of HA-MPC hybrid particles
[0137] The specific implementation method is the same as that of Example 1, except that the micellar casein concentrate (MCC) in step (1) is replaced by milk protein concentrate (MPC); the remaining steps are the same as those of Example 1 to obtain HA-MPC hybrid particles.
[0138] The hybrid particles prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to particle size and zeta potential measurements, Fourier transform infrared spectroscopy (FTIR) measurements, and scanning electron microscopy observations. The results are as follows:
[0139] 1. Measurement results of particle size and zeta potential
[0140] To evaluate whether the above proteoglycan complexes exhibited the expected particle characteristics and to assess their potential as Pickering emulsifiers, the particle size and surface potential of MCC and HA-MCC complexes were measured.
[0141] The results are shown in Table 1:
[0142] Table 1 Particle size and zeta potential of hybrid particles
[0143]
[0144] As shown in Table 1, despite the negative net surface charge of MCC and HA, the addition of HA resulted in an increase in particle size, indicating that protein-polysaccharide interactions not only promote complex formation but also affect the particle size distribution. The zeta potential of the complex increased and was between that of pure MCC and HA. Notably, the zeta potential of the HA-MCC complex was dominated by HA, suggesting that HA may interact with positively charged regions on MCC. HA chains may extend to the surface of MCC particles rather than being fully embedded or simply covering them. These findings highlight the role of hydrogen bonding and electrostatic interactions in the formation of HA-MCC hybrid particles, which hold promise as protein-polysaccharide Pickering emulsifiers.
[0145] According to the particle size and distribution, samples with a particle size of about 250 nm were selected to further investigate their interfacial properties, namely, the HA-MCC hybrid particles obtained in Example 1, Example 2 (HA molecular weight of 100 kDa), Example 3, and Example 4, and the pectin-MCC hybrid particles prepared in Comparative Example 2 (pectin, diluted 50 times).
[0146] 2. Results of Fourier transform infrared spectroscopy (FTIR)
[0147] Figure 1 The results showed that the hydrogen bond-related peaks of -OH groups in the spectra of MCC, HA with a molecular weight of 100 kDa, and HA with a molecular weight of 400 kDa appeared at 3280.82 cm-1 、3284.80cm -1 and 3261.03cm -1 When HA with a molecular weight of 100 kDa and an addition amount of 0.1% was used to prepare HA-MCC hybrid particles (Example 4), HA with a molecular weight of 100 kDa and an addition amount of 1.0% was used to prepare HA-MCC hybrid particles (Example 2), HA with a molecular weight of 400 kDa and an addition amount of 0.1% was used to prepare HA-MCC hybrid particles (Example 3), and HA with a molecular weight of 400 kDa and an addition amount of 1.0% was used to prepare HA-MCC hybrid particles (Example 1), the -OH stretching vibration peaks in the composite spectrum moved to 3280.62 cm-1, ... -1 、3274.16cm -1 、3273.58cm -1 and 3271.79cm -1 , which indicates that hydrogen bonds are formed between the amino and carboxyl groups of MCC and the hydroxyl groups of HA, because hydrogen bonds tend to reduce the stretching vibration frequency. In addition, the characteristic peaks of amide I (C=O stretching) and amide II (-NH2 bending and Cn stretching) of MCC are located at 1639.79 cm -1 and 1513.19cm -1 The formation of HA-MCC complex caused the peak of amide I to shift to 1640.56 cm -1 、1641.12cm -1 、1644.52cm -1 and 1644.56cm -1 , the peak shift of amide II is 1514.25 cm -1 、1532.79cm -1 、1515.62cm -1 and 1515.06cm -1 These changes suggest the existence of electrostatic interactions and hydrogen bonds between MCC and HA.
[0148] Figure 2 The results showed obvious morphological differences between the lyophilized MCC solution and the HA-MCC hybrid particles. The lyophilized MCC solution showed a layered network structure, which gradually transitioned to a rod-like network structure with the addition of HA. This transition became increasingly obvious with increasing HA concentrations. These findings suggest that the interaction between HA and MCC may lead to the formation of HA-MCC complexes, and the polysaccharide chains of HA may form a protective layer on the surface of MCC particles. The presence of HA not only enhances the electrostatic repulsion but also introduces steric hindrance, thereby limiting the aggregation of MCC particles.
[0149] Example 6: Preparation of a high internal phase emulsion gel with 75% (v / v) oil phase
[0150] The HA-MCC hybrid particles obtained in Example 1 were used as the aqueous phase solution. 10 mL of the HA-MCC hybrid particles aqueous phase solution obtained in Example 1 was poured into a 100 mL plastic beaker and slowly added into 30 mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / min). At the same time, a disperser (T10, IKA) was used for high shear dispersion at a shear rate of 10,000 rpm. The process included 1 minute of shearing, followed by a 10-second pause and repeated operations. The entire process lasted about 20 minutes, and a high internal phase emulsion gel containing 75% (v / v) oil phase was successfully obtained.
[0151] Example 7: Preparation of a high internal phase emulsion gel containing 80% (v / v) oil phase
[0152] The HA-MCC hybrid particles obtained in Example 1 were used as the aqueous phase solution. 10 mL of the HA-MCC hybrid particles aqueous phase solution obtained in Example 1 was poured into a 100 mL plastic beaker and slowly added into 40 mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / min). At the same time, a disperser (T10, IKA) was used for high shear dispersion at a shear rate of 10,000 rpm. The process included 1 minute of shearing, followed by a 10-second pause and repeated operations. The entire process lasted about 20 minutes, and a high internal phase emulsion gel containing 80% (v / v) oil phase was successfully obtained.
[0153] Example 8: Preparation of a high internal phase emulsion gel containing 85% (v / v) oil phase
[0154] The HA-MCC hybrid particles obtained in Example 1 were used as the aqueous phase solution. 7.5 mL of the HA-MCC hybrid particles aqueous phase solution obtained in Example 1 was poured into a 100 mL plastic beaker and slowly added into 42.5 mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / min). At the same time, a disperser (T10, IKA) was used for high shear dispersion at a shear rate of 10,000 rpm. The process included 1 minute of shearing, followed by a 10-second pause and repeated operations. The entire process lasted about 20 minutes, and a high internal phase emulsion gel containing 85% (v / v) oil phase was successfully obtained.
[0155] Example 9: Preparation of 50% (v / v) oil phase emulsion gel
[0156] The HA-MCC hybrid particles obtained in Example 1 were used as the aqueous phase solution. 20 mL of the HA-MCC hybrid particles aqueous phase solution obtained in Example 1 was poured into a 100 mL plastic beaker and slowly added into 20 mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / min). At the same time, a disperser (T10, IKA) was used for high shear dispersion at a shear rate of 10,000 rpm. The process included 1 minute of shearing, followed by a 10-second pause and repeated operations. The entire process lasted about 20 minutes, and an emulsion gel containing 50% (v / v) oil phase was successfully obtained.
[0157] Example 10: Preparation of 20% (v / v) oil phase emulsion gel
[0158] The HA-MCC hybrid particles obtained in Example 1 were used as the aqueous phase solution. 40 mL of the HA-MCC hybrid particles aqueous phase solution obtained in Example 1 was poured into a 100 mL plastic beaker and slowly added into 10 mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / min). At the same time, a disperser (T10, IKA) was used for high shear dispersion at a shear rate of 10,000 rpm. The process included 1 minute of shearing, followed by a 10-second pause and repeated operations. The entire process lasted about 20 minutes, and an emulsion gel containing 20% (v / v) oil phase was successfully obtained.
[0159] Example 11: Preparation of high internal phase emulsion gel
[0160] The hybrid particles prepared in the above-mentioned Example 2 (HA molecular weight is 100kDa), Example 3, and Example 4 are used as the aqueous phase solution. 10mL of the hybrid particle aqueous phase solution is poured into a 100mL plastic beaker and slowly added into 30mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / minute). At the same time, a disperser (T10, IKA) is used for high shear dispersion with a shear rate of 10,000rpm. The process includes 1 minute of shearing, then pausing for 10 seconds, and repeating the operation. The whole process lasts for about 20 minutes to obtain a high internal phase emulsion gel containing 75% (v / v) oil phase. Comparative Example 4: Preparation of an emulsion gel with 75% (v / v) oil phase using pectin-MCC hybrid particles as a particle emulsifier
[0161] The pectin-MCC hybrid particles prepared in Comparative Example 2 (pectin, diluted 50 times) were used as the aqueous phase solution. 10 mL of the aqueous phase solution of the pectin-MCC hybrid particles obtained in Comparative Example 2 was poured into a 100 mL plastic beaker and slowly added to 30 mL of soybean oil (oil phase) using a constant flow pump (HL-2S, Qingpu Huxi) (60 drops / minute). At the same time, a disperser (T10, IKA) was used for high shear dispersion at a shear rate of 10,000 rpm. The process included 1 minute of shearing, followed by a 10-second pause, and repeated operations. The entire process lasted about 20 minutes, and an emulsion gel containing 75% (v / v) oil phase was obtained. The results are shown in FIG. Figure 3 shown.
[0162] from Figure 3 It can be seen that the emulsion gel containing 75% (v / v) oil phase obtained in Comparative Example 4 has the oil phase and the water phase in a stratified state.
[0163] The emulsion gels prepared in the above-mentioned Examples 6 and 11 were tested for strength, rheological properties, water holding capacity (WHC) and oil holding capacity (OHC), stability and microstructure. The test results are as follows:
[0164] 1. Determination of gel strength and water holding capacity (WHC) and oil holding capacity (OHC)
[0165] Table 2 shows the WHC values of HA-MCC-stabilized HIPE gels formulated with different HA concentrations and molecular weights. The WHC of samples containing 1.0% HA exceeded 90%, and HIPE gels stabilized with 1.0% 400kDa HA-MCC showed the highest WHC. This suggests that HIPE gels with a 400kDa HA concentration of 1.0% may have better 3D printing performance compared with HIPE gels containing 0.1% 100kDa HA and pure MCC. The enhancement of WHC can be attributed to the formation of HA-MCC composite particles, which have a larger specific surface area and surface-extended HA chains, promoting greater water binding capacity. The increase in WHC observed in HIPE gels with higher HA concentrations may be due to the transformation of HA from a single molecule in water to the formation of a three-dimensional network structure with increasing concentration. The strong water binding ability of HA further strengthens the interaction between the HA-MCC complex and water molecules. Low molecular weight HA usually adopts a rigid rod-like structure, while high molecular weight HA produces a more flexible chain-like structure. For flexible structures, each polysaccharide chain exhibits obvious swelling of water molecules. The chain entanglement of high molecular weight HA forms a network structure, which can transmit tension under external force and maintain the integrity of the network, thereby inhibiting water migration and achieving higher WHC. In addition, high molecular weight HA has many exposed hydrogen bonding sites, allowing strong interaction with water molecules, further reducing water migration and enhancing WHC.
[0166] Oil content analysis confirmed that all HIPE gels reached 100% heat content without oil phase separation under centrifugal conditions, highlighting the superior emulsification ability of MCC. Incorporation of HA on HA-MCC particles enhanced chain entanglement and interfacial viscoelasticity, significantly improving gel stability. Unlike single biopolymer adsorption, which forms a weak interfacial film, HA-MCC complexes generate thicker and more robust networks that provide excellent oil droplet protection during centrifugal dehydration. This dense structure prevents oil phase separation and ensures the homogeneity and stability of the emulsion. The enhanced oil-water interface achieved by HA-MCC complexes is critical to maintaining the integrity of the emulsion, especially in applications such as 3D printing, where stability under mechanical stress directly affects performance and reliability.
[0167] Table 2 Test results of gel strength and water holding capacity (WHC)
[0168]
[0169] 2. Rheological properties results
[0170] like Figure 4 As shown in Figure a, both MCC and HA-MCC stabilized HIPE-gels exhibit shear thinning behavior in the linear viscoelastic region (LVR), and the viscosity decreases with increasing shear rate, belonging to pseudoplastic fluids. The viscosity of HA-MCC stabilized HIPE gels is higher than that of MCC stabilized gels, and the viscosity increases with increasing HA concentration and molecular weight. The entanglement of hyaluronic acid chains on MCC particles enhances gel stability and improves interlayer adhesion during printing.
[0171] The apparent viscosity of HIPE gels was analyzed using a power law model (Table 3), where K is the consistency coefficient reflecting viscosity and n is the flow behavior index representing pseudoplasticity. The n values for all samples were well below 1, confirming their shear thinning behavior. The high R2 values (0.948-0.997) indicated that the model accurately described the rheological properties of the gels. Notably, K increased with increasing polysaccharide concentration and molecular weight, reflecting stronger crosslinking between HA polysaccharide chains and MCC particles. This enhanced network structure significantly increased the apparent viscosity of the gel, consistent with experimental observations. These findings highlight the key role of molecular weight and concentration in regulating gel viscosity and stability.
[0172] Table 3 Apparent viscosity of HIPE gel
[0173]
[0174] The 3-ITT test evaluated the viscosity behavior of the emulsion gel under different shear conditions, simulating the extrusion dynamics. The results showed that under high shear, the viscosity decreased, allowing smooth extrusion, and after the shear was removed, the viscosity recovered, indicating that strong structural modification is essential for interlayer adhesion in 3D printing. The viscosity increased with increasing HA concentration and molecular weight ( Figure 4 (b), which is due to the HA chain entanglement and enhanced steric hindrance, which improves the interfacial viscoelasticity. These properties support efficient layer stacking, rapid post-extrusion molding, and improve the accuracy and structural integrity of the printed structure.
[0175] Creep recovery testing evaluates the gel’s resistance to deformation, a critical property for 3D printing applications. Figure 4 As shown in Figure 5c, MCC-stabilized HIPE gels exhibit rapid strain under stress and then stabilize after its removal, demonstrating recovery. Increasing polysaccharide concentration and molecular weight enhances the robustness of the network and reduces fluidity and peak strain. In HA-MCC-stabilized gels, these factors promote greater chain entanglement, strengthening the gel network and further improving deformation resistance. The resulting lower peak strain indicates reduced fluidity, which is beneficial for 3D printing by improving structural stability and precision. Compared to MCC alone, HA-MCC gels have superior mechanical strength and elasticity, minimizing permanent deformation under stress. These improvements are critical for producing reliable, durable printed structures.
[0176] The self-supporting ability of 3D printed materials is crucial to maintaining the stability of layer-by-layer stacking structures. Dynamic viscoelasticity is a key indicator, where the storage modulus (G′) reflects the elastic properties of the material and its ability to support it after printing, while the loss modulus (G″) represents the flow resistance under stress. Figure 4 Medium D and Figure 4Figure e shows the frequency-dependent responses of G′ and G″ at a constant shear strain of 0.1% (within the linear viscoelastic region, LVR). G′ consistently exceeds G″ at all tested frequencies, indicating that MCC and HA-MCC-stabilized HIPE gels exhibit solid-like elastic behavior. The G′ values of HA-MCC-stabilized HIPE gels increase with increasing polysaccharide concentration and molecular weight, and further increase with increasing frequency. These trends indicate that the self-supporting ability increases with increasing HA concentration. At the same polysaccharide concentration, longer HA chains produce the highest G′ values, which is due to their chain conformation and network formation, which strengthens the gel structure. Notably, 1.0% 400 kDa HA-MCC-stabilized HIPE gels exhibit the strongest self-supporting properties. This superior elasticity is critical for optimizing 3D printing materials. High G′ values improve interlayer adhesion and structural stability during the printing process, enhancing the quality and durability of the final product. The reinforcement provided by longer HA chains further emphasizes their role in molding materials suitable for reliable, high-precision 3D printing.
[0177] The viscoelasticity of a material is rigorously evaluated by the dynamic loss tangent (tan δ = G″ / G′), which reflects the internal friction and energy dissipation under applied stress. In 3D printing, lower tan δ values indicate greater internal friction and energy loss, which affects printing efficiency and durability of printed parts. Figure 4 As shown in (f), MCC- and HA-MCC-stabilized HIPE gels exhibit tan δ values below 1, and the storage modulus (G′) always exceeds the loss modulus (G″), indicating that elastic behavior dominates. Increasing the polysaccharide concentration in the HA-MCC-stabilized HIPE gel further reduces tan δ and enhances the gel elasticity. This elasticity is critical to maintaining the structural integrity of the printed object as it ensures stability during and after printing. However, too low tan δ values may lead to extrusion challenges, such as increased viscosity or filament breakage, which may disrupt the printing process.
[0178] 3. Gel stability results
[0179] We further studied the effect of HA on the stability of HIPE gels. Figure 5Figures AF show the integrated transmittance curves of different HIPE gels over time under 865 nm near-infrared collimated light. The position of 130 mm on these curves corresponds to the bottom of the sample, while approximately 105 mm marks the top. The transmittance of an emulsion is inversely proportional to the droplet concentration. Higher transmittance generally reflects lower droplet concentrations, while lower transmittance indicates higher concentrations. When near-infrared light is passed through the HIPE gel, generally low transmittance is observed, indicating that the gel structure is tight and opaque. However, if the structure of the HIPE-gel is disrupted by centrifugal forces, the oil droplets tend to rise, while the aqueous phase settles to the bottom. This disruption of the structure increases the transmittance because the aqueous phase is concentrated in the lower part. Figure 5 In middle AF, the initial profile (red line) shows very low bottom transmittance, indicating that the HIPE gels were initially homogeneous and opaque, except for the HIPE gel stabilized by 1.0% 400 kDa HA-MCC. After centrifugation at 3000 rpm for 150 min, the final curve (green line) shows a significant increase in bottom transmittance, indicating that the gel structure was destroyed and the aqueous phase separation resulted in higher transmittance.
[0180] Figure 5 The results of the medium AF clearly show that in HA-MCC-stabilized HIPE gels, the difference in the transmittance spectra during centrifugation is reduced, indicating that HA significantly enhances the stability of the HIPE gels. This enhanced stability can be attributed to the network formed by the entangled HA chains, which enhances the interfacial viscoelasticity of the emulsion droplets. When an external force is applied, the HA chains slide relative to each other, transferring tension along the chains and dispersing it throughout the network through entanglement. This interfacial layer acts like an elastic net, tightly wrapping the emulsion droplets to prevent them from breaking under compression or vibration, thereby significantly improving the stability of the emulsion gel. In addition, at the same HA concentration, the HIPE-gels stabilized by longer HA chains (i.e., 400 kDa HA-MCC) show significantly less strength changes under external forces. It is noteworthy that the HIPE gels stabilized by 1.0% 400 kDa HA-MCC, which have longer HA chains and higher concentrations, show little change during accelerated centrifugation, with almost no change in transmittance. This shows that these HIPE gels have significant resistance to aggregation even under high-speed centrifugation.
[0181] 4. Results of determination of gel morphology and microstructure
[0182] HA-MCC stabilized gels adhered to the sample vials at different HA concentrations and molecular weights, showing a self-supporting structure ( Figure 6 (a). Figure 6As shown in b, the microstructure of the emulsion gel shows that MCC and HA interact in the continuous phase to form a gel network. The red oil phase droplets are wrapped by the green continuous phase composed of MCC or HA-MCC complex. As the HA concentration and molecular weight increase, the oil droplet size in the gel decreases and the distribution becomes more uniform. This effect is due to the entanglement of HA polysaccharide chains at higher concentrations and molecular weights to form an intramolecular network, which strengthens the cross-linking interactions and steric hindrance between the polysaccharide chains around the droplets, resulting in a tighter interface structure. In addition, the negative charge of HA interacts with the surface charge of MCC, enhancing the electrostatic stability of the emulsion, effectively preventing droplet aggregation and making the droplet distribution more uniform. When the HA concentration is 1.0% (w / v), the droplets are smaller, and each droplet is completely wrapped by the surrounding HA-MCC complex. At the same HA concentration, the molecular weight of HA also plays a vital role in the structure of the gel. Among them, the droplet size of the emulsion gel prepared using the HA-MCC hybrid particles of Example 1 is the smallest and the distribution is the most uniform, as shown in Figure 1. Figure 6 This may be due to the longer chain length of H-HA, which allows for greater chain entanglement, leading to a stronger network structure and greater steric hindrance, thereby enhancing the stability of the emulsion.
[0183] 5. Swallowing performance
[0184] like Figure 7 As shown, for 0.1% HA samples with two different molecular weights, when the spoon is tilted, both samples can slide down slowly, and only a small amount of food residue is observed. This shows that both samples belong to IDDSI Level 4 (paste) food. At the same time, the residue of both samples on the spoon is less than that of other samples, indicating that the sample with a lower concentration of 0.1% has less HA residue during swallowing, and has better swallowing performance, which can make the food bolus more compact during swallowing and avoid the food bolus being broken into fragments during swallowing, making it more suitable for people with dysphagia.
[0185] Example 12: High internal phase emulsion gels of different colors
[0186] 1. Preparation of yellow high internal phase emulsion gel
[0187] Curcumin (0.5 mg / mL) was dissolved in soybean oil and yellow HIPE gel was prepared according to Example 6. Figure 8 (Figure above).
[0188] Curcumin (0.5 mg / mL) was dissolved in soybean oil, and three yellow HIPE gels were prepared according to Example 11.
[0189] 2. Preparation of pink high internal phase emulsion gel
[0190] Anthocyanin (0.1 g / mL) was dissolved in MCC and pink HIPE gel was prepared according to Example 6. Figure 8 (Figure below).
[0191] The emulsion gels prepared in the above-mentioned Examples 6, 11 and 12 were subjected to 3D printing performance testing, and the test results are as follows:
[0192] like Fig. 9 As shown, the gel stabilized by MCC particles alone remained liquid after printing and could not maintain its designed shape. When HA-MCC hybrid particles stabilized the gel at low HA concentration (0.1% w / v), the gel could initially be extruded but lacked structural stability and eventually collapsed. At higher HA concentrations (1.0% w / v), the gel could be printed into a stable, well-defined structure that closely resembled the designed model, with enhanced texture and durability.
[0193] The high internal phase emulsion gel of Example 6 and the high internal phase emulsion gel obtained in Example 11 using the hybrid particles of Example 4 as the water phase, the hybrid particles of Example 3 as the water phase, or the hybrid particles of Example 2 (HA molecular weight of 100 kDa) as the water phase were measured for 3D printing accuracy and stability.
[0194] The results are shown in Table 4. The high internal phase emulsion gel printing accuracy and stability obtained in Example 6 are the highest.
[0195] Table 4 Accuracy and stability of 3D printed samples
[0196]
[0197] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing hyaluronic acid-micellar casein concentrate hybrid particles using micellar casein concentrate and sodium hyaluronate, characterized in that: The method is: Dispersing micellar casein concentrate in water, mixing and homogenizing; adding sodium hyaluronate, stirring, and obtaining HA-MCC hybrid particles; The molecular weight of the sodium hyaluronate is 100 to 1090 kDa; the amount of the sodium hyaluronate added is 0 to 1.0% w / v; The final concentration of the micellar casein concentrate in water is 1% to 5% w / w.
2. The method according to claim 1, characterized in that The molecular weight of the sodium hyaluronate is 200-600 kDa; Preferably, the molecular weight of the sodium hyaluronate is 400 kDa; Preferably, the added amount of sodium hyaluronate is 1.0% w / v.
3. HA-MCC hybrid particles prepared by the method of claim 1 or 2.
4. Application of the method according to claim 1 or 2 or the HA-MCC hybrid particles according to claim 3 in the fields of food, health products, cosmetics, daily chemicals or biomedicine; Optionally, the application is to embed and deliver bioactive substances, gel liquid oils; or prepare emulsions, foams, emulsion gels or high internal phase emulsion gels, etc.; Optionally, the application includes using the HA-MCC hybrid particles according to claim 3 for the preparation of food, health products, biopharmaceuticals or daily chemical products.
5. A method for preparing an emulsion gel using the HA-MCC hybrid particles according to claim 3, characterized in that: The method is: The HA-MCC hybrid particles according to claim 3 are used as the aqueous phase, the aqueous phase is mixed with the oil phase, and dispersed by high-speed shearing to obtain an emulsion gel; Optionally, the volume ratio of the oil phase to the water phase is (0:100) to (85:15), but not 0.
6. A method for preparing a high internal phase emulsion gel using the HA-MCC hybrid particles according to claim 3, characterized in that: The method is: The HA-MCC hybrid particles according to claim 3 are used as the aqueous phase, the aqueous phase is mixed with the oil phase, and a high internal phase emulsion gel is obtained by high-speed shear dispersion; the volume ratio of the aqueous phase to the oil phase is (0:100) to (15:85), but not 0; Preferably, the volume ratio of the water phase to the oil phase is 1:
3.
7. An emulsion gel or high internal phase emulsion gel obtained by the method of claim 5 or 6.
8. Use of the high internal phase emulsion gel according to claim 7 in a fat-soluble active ingredient carrier; Optionally, the fat-soluble active ingredients include, but are not limited to, curcumin, β-carotene, astaxanthin, lycopene, vitamin E, n-3 fatty acids, vitamin A, resveratrol, and capsaicin.
9. Use of the HA-MCC hybrid particles according to claim 3 or the high internal phase emulsion gel according to claim 7 in 3D printed food; Optionally, the application is to use a 3D printer to perform emulsion gel 3D printing using the high internal phase emulsion gel according to claim 7.
10. A 3D printed food based on the high internal phase emulsion gel according to claim 7, characterized in that: The 3D printed food is obtained by 3D printing using the high internal phase emulsion gel according to claim 7; Optionally, the food is easy-to-swallow food.
Citation Information
Patent Citations
Structural protein / hyaluronic acid composite micro-nano particle, particle hydrogel material and application
CN115521627A
Preparation of limited compliance soft particle and application of limited compliance soft particle as Pickering particle
CN118476605A
Casein-hyaluronic acid 3D milk foam product and preparation method thereof
CN118902062A
Casein nanoparticle
US20090280148A1
Casein nanoparticle
US20100143424A1